Analysis of Local Government Financial Budgeting with Standard Spending Analysis (Study Case Kubu Raya Regency APBD Year 2018) - Yuswanto, Resky Andika (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
The purpose of this study is to determine the preparation of the Shopping Standards Analysis (ASB) to achieve Performance Based Budgeting which has become mandated in the law adopted in Kubu Raya Regency. The data used is secondary data in the form of a Budget Implementation Document (DPA) from 36 Regional Government Unit (SKPD) Kubu Raya Regency. Data is a sample of general activities held in 2018. Data is processed with several analytical tools, namely the regression method, benchmark and fairness assessment of spending. The concept of Activity Based Costing is used to determine fixed costs and variable costs combined with regression analysis. Statistics Description is used to determine averages, lower and upper limits. The result of data processing is the compilation of 23 types of ASB with the formulation Y = a + bx or Total Expenditures = Fixed Expenditure + Variable Expenditures x Spending Drivers. SKPD in Kubu Raya Regency is possible to implement ASB to achieve more effective and efficient budgeting. REFERENCES APKASI. (2009). Penyusunan Analisis Standar Belanja: Pengalaman Praktis di Pemerintahan Daerah. Yogyakarata: Asosiasi Pemerintah Kabupaten Seluruh Indonesia.Bastian, I. (2006). Akuntansi Sektor Publik: Suatu Pengantar. Jakarta: Erlangga.Carter, W. K. (2006). Cost Accounting. Mason: Thomson Custom Solution.Cooper, W. W., Seiford, L. M., & Zhu, J. (2011). Data Envelopment Analysis: History, Model and Interpretation. Austin: McCombs School of Business, University of Texas at Austin.Creswell, J. W. (2016). Research Design: Pendekatan Metode Kualitatif, Kuantitatif dan Campuran Edisi Keemoat. Yogyakarta: PUSTAKA PELAJAR.Darmayasa, I. N. (2013). Analisis Standar Belanja (ASB) untuk Mencapai Penganggaran Berbasis Kinerja pada Kabupaten Jembrana. Prosiding Simposium Nasional Akuntansi Vokasi ke-2, 154 - 162.Dr. Suliyanto. (2014). Statistika Non Parametrik. Yogyakarta: ANDI Yogyakarta.Fadilah, S. (2009). ACTIVITY BASED COSTING (ABC) SEBAGAI PENDEKATAN BARU UNTUK MENGHITUNG ANALISIS STANDAR BELANJA (ASB) DALAM PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DAERAH (APBD). JURNAL TELAAH & RISET AKUNTANSI, 54 - 78.Fithri, M. (2018). Analisis Model Analisa Standar Belanja (Studi Pada Daerah Istimewa Yogyakarta).Garrison, H. R., Noreen, W. E., & Brewer, C. P. (2010). Managerial Accounting 13/e. New York: McGraw-Hill/Irwin.Garrison, H., & Brewer, P. (2007). Managerial Accounting. Mcgraw-Hill Companies.Ghozali, I. (2011). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 19. Edisi kelima. Semarang: Universitas Diponegoro.Gunawija, R. (2017). EVALUASI KEWAJARAN ANGGARAN KEGIATAN MELALUI ANALISIS STANDAR BELANJA DENGAN PENDEKATAN ACTIVITY BASED COSTING DI INSTITUT AGAMA ISLAM NEGERI PONTIANAK. Jurnal Ekonomi Daerah (JEDA) Vol 5, No 3 (2017) , 1 - 15.Hasanah, N., & Fauzi, A. (2016). Akuntansi Pemerintahan. Jakarta: Penerbit IN MEDIA.Kawedar, W. (2008). Pendekatan Penganggaran Daerah dan Akuntansi Keuangan Daerah / Buku 1. Semarang: Badan Penerbit Universitas Diponegoro.Liwaul, Rosika, Purwati, N. E., & Hamryati. (2017). Analysis of Performance-Based Budgeting System Implementation in Improving Organizational Effectiveness. IOSR Journal of Business and Management (IOSR-JBM) , 62 - 70.Lopez, J. J., Aparicio, J., Gimenez, D., & Pastor, J. T. (2014). Benchmarking and Data Envelopment Analysis. An Approach Based on Metaheuristics. Procedia Computer Science Volume 29, 390–399.Maradhona, R. (2010). Analisis Implementasi Analisa Standar Belanja (ASB) dalam Penyusunan Anggaran Bebasis Kinerja pada Dinas Pertanian Tanaman dan Hortikultura Kabupaten Madiun Tahun 2010.Mardiasmo. (2009). Akuntansi Sektor Publik. Yogyakarta: CV. Andi Offset.Pemerintah Kabupaten Bulungan. (2019, Januari 10). Bulungan.go.id. Retrieved from Arsip Berita: https://bulungan.go.id/v5/index.php/kontak-kami/938-istilah-skpd-jadi-opdPemerintah Provinsi Jawa Tengah. (2018, September 24). Bappeda Prov. Jateng. Retrieved from Rencana Kerja dan Anggaran (RKA) – Bappeda Prov. Jateng: bappeda.jatengprov.go.id › rencana-kerja-dan-anggaran-2016Sekaran, U. (2016). Research Methods for Business: A Skill-Building Approach Seventh Edition. Chichester: John Wiley & Sons,.Shim, J. K., & Siegel, J. G. (2000). Budgeting: Pedoman Lengkap Langkah-Langkah Penganggaran. Jakarta: Penerbit Erlangga.Siregar, S. (2017). Statistik Parametrik untuk Penelitian Kuantitatif. Jakarta: Bumi Aksara.Sprouse, R. T., & Maurice, M. (1962). A Tentative Set of Broad Accounting Principles for Business Enterprises. Accounting Research Study No.3, 25.Sugiyono. (2011). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta CV Bandung.Susenohaji. (2018). Pengembangan Model Analisis Standar Belanja Pemerintah Kota Malang (Studi Kasus Kegiatan Bimbingan Teknis). 2 - 16.Usman, H., & Purnmomo, S. A. (2006). Pengantar Statistika. Jakarta: PT Bumi Aksara.Walpole, R. E. (1993). Pengantar Statistika. Jakarta: PT Gramedia Pustaka Utama.Wijayanti, W. A., Muluk, M. R., & Nurpratiwi, R. (2012). Perencanaan Anggaran Berbasis Kinerja di Kabupaten Pasuruan. Wacana – Vol. 15, No. 3 (2012), 10 - 17.